Use of FAO-56 and scintillometer to estimate evapotranspiration of grain sorghum (Sorghum bicolor L.) and its components: soil evaporation and plant transpiration - Lopez Avendaño, Jesus Enrique; César Rodríguez, Julio; Martínez Gallardo, José Ángel; Lizárraga Jiménez, Ramón; Díaz Valdés, Tomás (REVISTA TERRA LATINOAMERICANA, 2019)
Estimating evapotranspiration (ETc) is essential for water planning and management in agricultural areas, particularly in arid and semi-arid regions; ETc partitioning into soil evaporation (E) and plant transpiration (T) would allow the use of more eff icient water management strategies. The aims of the present study were to estimate daily evapotranspiration of sorghum and its components, using the FAO-56 method with the dual crop coeff icient (dual Kc) approach and scintillometer method, and to determine the single crop coeff icient (Kc) and basal crop coeff icient (Kcb) values for different development seasons. Results have shown that using the dual Kc approach allows reasonable simulation of ETc in comparison to values estimated using the scintillometer method. ETc estimated with both methods was 413.8 and 406.3 mm, respectively, resulting in a 1.8% overestimation for FAO-56. Root mean square error (RMSE) was 0.584 mm d-1 and Willmott’s agreement coeff icient (d) was 0.91. Evaporation estimated with FAO-56 was 17.1% of ETc, while with the scintillometer it was 21.6% of ETc. The RMSE of the estimated E values was 0.397 mm d-1 and d = 0.94, while, when comparing T, calculated RMSE was 0.371 mm d-1 and d = 0.98. Kc values estimated with the FAO-56 method were 0.68, 1.06 and 0.4 for initial, middle and end season of the crop, while for the scintillometer, values were 0.75, 0.94 and 0.41, respectively.